Impact of Corporate Governance Structure on Firm’s Dividend Policy of Non Financial Firms (Evidence from Pakistan Stock Exchange) - Ullah, Raza; Shah, Dr. Farooq; Khan, Dr. Muhammad Irshad; Islam, Zia ul; Hassan, Zia ul (The journal of contemporary issues in business and government, 2021)
The present study has been conducted to examine the effect of corporate governance on the firm’s dividend payout. The study was conducted in the non financial sector of Pakistan. The study was conducted in the PSX 100 index. On the basis of the nature, 65 non financial firms were included as the sample size. The study has used data collected from their website from 2011 to 2018. The study has used diagnostic models for the selection of the final model of analysis. The results showed that OLS has been recommended in the case of small and large firms while fixed effect model can be used for the medium firms. The findings of small size firms showed that 1) board size has significant effect on dividend payout while CEO compensation and board independence have insignificant effect. The results of medium size firm showed that 2) family ownership has significant effect on dividend payout in medium and large firms while CEO ownership has significant effect on dividend payout in small, medium and large firms. The results of third model showed that 3) disclosure policy and shareholders rights have significant effect on dividend payout ratio. The findings of the study recommends that the firms should diversify their board and increase the size as it will help in attracting new investors.